Pirate Trails: Tracking the Illicit Financial Flows from Pirate Activities off the Horn of Africa (World Bank, 2015)
Traditionally piracy has produced sentimental notions of adventure, freedom, and independence. However, piracy is a criminal act and often involves high levels of violence that can have a devastating impact on the victims. 21st Century piracy has evolved into a highly complex system involving a cast of characters, each motivated by a mix of economic and social reasons. While the focus of the international community has been on dealing with piracy through counter piracy operations that include naval, air, and military operations, this book attempts to understand the illicit financial flows from the proceeds of piracy and to espouse the cause for the detection, disruption, and confiscation of proceeds from acts of piracy.